Perbandingan Pemikiran Mohammad Natsir dan Mohammed Arkoun Tentang Relasi Agama dan Negara - Zikra Nazhifah (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2021)
In casees, of debates related to religious and state associations. Particulary in Indonesia, these conflicts often occur in political spheres. Like, the appearance of political parties wanting to replace the nation’s ideology with religion. In this article will be considered how Mohammad Natsir and Mohammed Arkoun view Islamic and state relations. And then we’ll see common points and different ducks the second thought of those characters. In doing research the author use your historically and philosophical for actual and comprehensive data. In this study authors found similarities to the thought of Natsir and Arkoun, in their thinking agreed with the a substantiating flow, who belive that Islam had never advocated the establishment of an Islamic State, it’s just how both the ideology and the laws of the country contain values that are relevant to the doctrine of Islam. Whereas the difference in thinking of the two figure lies in the degree to which their ideas and actions explore the issue if Islamic and state relation.